Evaluation of The Effectiveness of New Connector Road in Reducing Congestion through VISSIM Simulation - Rimbawan, Ratno Damar; Prasetyo, Yohanes Pracoyo Widi; Sunarko (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2025)
Rapid motorization in Indonesia has intensified congestion not only in metropolitan areas but also in secondary urban centers such as Genteng District, Banyuwangi, where a single arterial corridor supports commercial and inter-district mobility. However, research addressing congestion mitigation in semi-urban road networks through strategic traffic diversion remains limited. This study evaluates the effectiveness of an alternative road routing strategy in reducing congestion along Jalan Gajah Mada using VISSIM-based microscopic simulation. Two scenarios were compared: the existing condition and a diversion strategy rerouting vehicles through Jalan KH Wahid Hasyim. Key performance indicators—average travel time, speed, queue length, and level of service (LoS)—were analyzed. Results reveal significant performance improvements despite a longer physical route: travel time decreased by 25.8%, speed increased by 143.6%, queue length reduced by 44.9%, and LoS improved from E to D. These findings highlight the potential of strategically planned traffic diversion to enhance mobility in semi-urban settings. The study is limited to peak-hour traffic and a single diversion scenario, suggesting the need for further evaluation with multimodal and multi-scenario analyses.